Molecular dissociation of the role of PSD-95 in regulating synaptic strength and LTD - Xu, Weifeng (2008)
PSD-95, a multi-domain protein enriched in the postsynaptic density, influences AMPA receptor (AMPAR) content at synapses and may play a critical role in LTD. Here we molecularly dissect the effects of PSD-95 on basal AMPAR-mediated synaptic responses and LTD using several complementary approaches. Our findings suggest that N-terminal domain mediated dimerization is important for PSD-95’s effect on basal synaptic AMPAR function whereas the SH(3)-GK domains in its C-terminal region are also necessary for localizing PSD-95 to synapses. Using a molecular replacement approach, we identify point mutants (Q15A, E17R) of PSD-95 that increase basal AMPAR-mediated synaptic responses to the same degree as wildtype PSD-95 yet block LTD. These point mutants increase the proteolysis of PSD-95 within its N-terminal domain. Several lines of evidence indicate that the resulting C-terminal fragment of PSD-95 functions as a dominant negative by binding to one or more of the critical signaling proteins required for LTD. Together our findings demonstrate that the effects of PSD-95 on basal AMPAR synaptic responses and LTD are dissociable. The N-terminal domain of PSD-95 is required for dimerization and appropriate synaptic enrichment of PSD-95 but alone does not influence synaptic function. The C-terminal portion of PSD-95 serves a dual function. It is also required to localize PSD-95 at the synapse and as a scaffold for critical downstream signaling proteins that are required for LTD.